1984
DOI: 10.1007/bf03348395
|View full text |Cite
|
Sign up to set email alerts
|

The endocrine pattern of late onset adrenal hyperplasia (21-hydroxylase deficiency)

Abstract: We describe 5 adult women with severe hirsutism due to late onset 21-hydroxylase deficiency. Diagnosis was performed on the finding of high serum 17-hydroxyprogesterone (17OHP) levels with a marked hyperresponse to an ACTH test. The endocrine study showed in most patients a gonadotropin behavior similar to that observed in classical polycystic ovary (PCO) syndrome. Prolactin levels were slightly increased in basal conditions and presented an exaggerated response to TRH stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In the past, we had demonstrated that 11β‐hydroxy‐androstenedione (a marker of adrenal androstenedione production) is increased in all patients with NCAH while only a minority of patients present also an increase of serum DHEAS 38 . Although the peripheral pattern of serum androgens is similar to that found in PCOS, 39–41 the mean serum levels of androstenedione and testosterone are generally higher in NCAH than in PCOS 7 …”
Section: Androgen Source In Ncahmentioning
confidence: 78%
“…In the past, we had demonstrated that 11β‐hydroxy‐androstenedione (a marker of adrenal androstenedione production) is increased in all patients with NCAH while only a minority of patients present also an increase of serum DHEAS 38 . Although the peripheral pattern of serum androgens is similar to that found in PCOS, 39–41 the mean serum levels of androstenedione and testosterone are generally higher in NCAH than in PCOS 7 …”
Section: Androgen Source In Ncahmentioning
confidence: 78%
“…Normal circulating levels of 17-hydroxyprogesterone (<3 mg/L) were used to exclude the diagnosis of nonclassic 21-hydroxylase deficiency (19). Clinical data and/or urinary cortisol (<60 mg/day) assessment were used to exclude the diagnosis of Cushing syndrome (20), and normal levels of prolactin (<25 ng/mL) used to exclude hyperprolactinemia (9).…”
Section: Methodsmentioning
confidence: 99%
“…Adrenal androgens are increased in NCAH. However, DHEAS is usually normal, while androstenedione, testosterone and dihydrotestosterone (DHT) are elevated (27,51,52). The CYP21A2 deficiency results in increased 17OHP levels regardless of the ACTH increase owing to the kinetics in the enzymatic steps.…”
Section: Biochemistry and Pathophysiologymentioning
confidence: 99%